2022
DOI: 10.1111/joes.12528
|View full text |Cite
|
Sign up to set email alerts
|

Financial development and income inequality: A meta‐analysis

Abstract: The voluminous empirical research on the effect of financial development on income inequality has yielded mixed results. In this paper, we collect 2127 estimates reported in 116 published studies that investigate the effect of financial development on income inequality. Although our initial tests for publication bias (which do not account for moderator variables) show that the current literature does not suffer from publication selectivity, once we control for a set of moderator variables, we find evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 106 publications
0
5
0
Order By: Relevance
“…The Panel root results given in Chletsos and Fatouros (2016). On the other side, economic growth indicates a positive and significant relationship with income inequality.…”
Section: Results and Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…The Panel root results given in Chletsos and Fatouros (2016). On the other side, economic growth indicates a positive and significant relationship with income inequality.…”
Section: Results and Analysismentioning
confidence: 92%
“…García-Peñalosa (1999) examined the employment's impact in association with the agriculture sector on income inequality in developed economies and developing economies as well and results indicated a lower level of income inequality in the agrarian sector followed by a high employment ratio in that particular sector, as the benefits through agricultural output assist the lower-income groups to enjoy a rise in income. Chletsos and Fatouros (2016) empirically analyzed the consequence of income inequality on economic development designing panel of 126 countries from 1968 to 2007 and the conclusion revealed a positive consequence in line with government revenues. Maestri (2012) studied the analogy of inflation and unemployment on income inequality for the Organization for Economic Co-operation and Development (OECD) and came up with the deduction that inflation caused a hike in income inequality in countries like the United States (USA) Germany and Sweden, while Canada experienced a diminishing trend in income inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chletsos and Sintos (2023) [ 30 ] proposed that the overall impact of financial development on income inequality averages to zero but varies systematically based on study characteristics. In contrast, Chletsos and Sintos (2022) [ 31 ] found that IMF programs are associated with increased income inequality for up to five years. Heimberger (2020) [ 32 ] utilized a new dataset with 1254 observations from 123 primary studies, employing meta-analysis and meta‐regression techniques, and discovered that financial globalization has a more significant and markedly stronger impact on increasing inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, inflation plays a substantial role in income distribution. Sintos (2023) [29] discovered that factors such as price stability, financial deepening, development level, state employment, and fiscal redistribution enhance income equality in a given country. Furthermore, low inflation strengthens the income-equalizing effect of fiscal redistribution.…”
Section: Some Other Factors That Affect the Inequalitymentioning
confidence: 99%
“…This can have various social, economic, and political implications. Factors contributing to income inequality can include differences in education, skills, employment opportunities, inheritance, and government policies (Chletsos, & Sintos, 2023). Income inequality can lead to various social and economic challenges, including reduced social mobility, increased poverty rates, and potential negative effects on overall economic growth.…”
Section: Concept Of Income Inequalitymentioning
confidence: 99%